Exposure to microplastics contaminated with pharmaceuticals and personal care products: Histological effects on Ucides cordatus - da Silva, Letícia Fernanda [UNESP]; Nobre, Caio Rodrigues [UNESP]; Moreno, Beatriz Barbosa; Pereira, Camilo Dias Seabra; Gonçalves, Alexandre Rodrigo Nascimento [UNESP]; do Nascimento, Nathalia Sales Soares [UNESP]; Marinsek, Gabriela Pustiglione [UNESP]; de Britto Mari, Renata [UNESP]; Simões, Fábio Ruiz; Carnaúba, José Hérelis; Choueri, Rodrigo Brasil; Gusso-Choueri, Paloma Kachel; et al. (Elsevier, 2024)
Pharmaceuticals and personal care products (PPCPs) are known to interact with microplastics (MPs) in aquatic environments, with substances such as the antimicrobial triclosan (TCS) and the synthetic hormone 17α-ethinylestradiol (EE2) being prevalent. These persistent contaminants are linked to toxic effects in aquatic organisms. This study aimed to investigate histological and morphometric changes in the gills of Ucides cordatus exposed to microplastics alone and microplastics contaminated with PPCPs. The experimental design included four treatment groups: 1) control (C), 2) virgin microplastics (MP), 3) microplastics fortified with triclosan (MPT), and 4) microplastics fortified with 17α-ethinylestradiol (MPE), with exposure durations of 3 or 7 days. Significant differences were observed in the histopathological indices for treatments with PPCP-fortified microplastics at 3 days (MPT and MPE) and 7 days (MPT). Notable pathologies included necrosis, fibrosis, and circulatory disorders. Exposure duration was significantly associated with morphometric changes, including secondary lamellar width in MPT and secondary lamellar length in MPE. These findings indicate that exposure to microplastics contaminated with PPCPs may impair the osmoregulatory and respiratory functions of Ucides cordatus.
Keywords: Antimicrobial; Contraceptive hormone; Crabs; Histopathology; Morphometry; Plastic pollution